The Benefits of Unnatural Amino Acid Incorporation as Protein Labels for Single Molecule Localization Microscopy - Laxman, Pooja; Ansari, Shirin; Gaus, Katharina; Goyette, Jesse (Frontiers in Chemistry, 2021)
Single Molecule Localisation Microscopy (SMLM) is an imaging method that allows for the visualisation of structures smaller than the diffraction limit of light (~200 nm). This is achieved through techniques such as stochastic optical reconstruction microscopy (STORM) and photoactivated localisation microscopy (PALM). A large part of obtaining ideal imaging of single molecules is the choice of the right fluorescent label. An upcoming field of protein labelling is incorporating unnatural amino acids (UAAs) with an attached fluorescent dye for precise localisation and visualisation of individual molecules. For this technique, fluorescent probes are conjugated to UAAs and are introduced into the protein of interest (POI) as a label. Here we contrast this labelling method with other commonly used protein-based labelling methods such as fluorescent proteins or self-labelling tags such as Halotag, SNAP-tags and CLIP-tags, and highlight the benefits and shortcomings of the site-specific incorporation of UAAs coupled with fluorescent dyes in single molecule localisation microscopy (SMLM).